2014
DOI: 10.3389/fpubh.2014.00083
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare for Persons with Intellectual and Developmental Disability in the Community

Abstract: Introduction: While there has been impressive progress in creating and improving community healthcare delivery systems that support people with intellectual and developmental disabilities (IDD), there is much more that can and should be done.Methods: This paper offers a review of healthcare delivery concepts on which new models are being developed, while also establishing an historical context. We review the need for creating fully integrated models of healthcare, and at the same time offer practical considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 21 publications
2
65
0
3
Order By: Relevance
“…In our sample, use of health services was more common among participants with mild and profound intellectual disability. Extensive research has shown the importance of health promotion and prevention activities for people with intellectual developmental disorders, as they can effectively improve health outcomes, promote participation in the patient's own health care and increase this population's access to health services(Ervin, Hennen, Merrick, & Morad, 2014). In Spain, a study found that people with severe and profound levels of intellectual disability used social healthcare services less than those with mild and moderate intellectual disability, although they had more medical and social needs(Verdugo et al, 2016).…”
mentioning
confidence: 99%
“…In our sample, use of health services was more common among participants with mild and profound intellectual disability. Extensive research has shown the importance of health promotion and prevention activities for people with intellectual developmental disorders, as they can effectively improve health outcomes, promote participation in the patient's own health care and increase this population's access to health services(Ervin, Hennen, Merrick, & Morad, 2014). In Spain, a study found that people with severe and profound levels of intellectual disability used social healthcare services less than those with mild and moderate intellectual disability, although they had more medical and social needs(Verdugo et al, 2016).…”
mentioning
confidence: 99%
“…Similarly, it is often assumed that the supervising clinician is aware of the individual patient's preferences and is in the practice of obtaining consent to student involvement. It is important to clarify this with any person receiving health care, particularly with individuals who are exceptionally marginalised and often not empowered in making choices about their own health care experiences . A combination of varied communication barriers (expressive or receptive), cognitive capabilities and lack of advocacy can result in the receipt of suboptimal health care.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to clarify this with any person receiving health care, particularly with individuals who are exceptionally marginalised and often not empowered in making choices about their own health care experiences. 4 A combination of varied communication barriers (expressive or receptive), cognitive capabilities and lack of advocacy can result in the receipt of suboptimal health care. Future health care providers can be alert to the needs of patients with DD and address them in the following ways, based on recommendations derived from our focus groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many health care systems around the world are still struggling with these issues, and various models have emerged [1,2,4].…”
Section: Introductionmentioning
confidence: 99%